2008
DOI: 10.1063/1.2989981
|View full text |Cite
|
Sign up to set email alerts
|

Probing the mechanisms of fibril formation using lattice models

Abstract: Using exhaustive Monte Carlo simulations we study the kinetics and mechanism of fibril formation using lattice models as a function of temperature ͑T͒ and the number of chains ͑M͒. While these models are, at best, caricatures of peptides, we show that a number of generic features thought to govern fibril assembly are captured by the toy model. The monomer, which contains eight beads made from three letters ͑hydrophobic, polar, and charged͒, adopts a compact conformation in the native state. In both the single-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(125 citation statements)
references
References 53 publications
(81 reference statements)
5
120
0
Order By: Relevance
“…(a) Simple models: the orientable stick model (19) and the sphero-cylindrical model (20). (b) Phenomenological models: the lattice model (21), Caflisch model (22), and Shea model (23). (c) Systematic coarse graining: a coarse-grained polyalanine chain (24).…”
Section: Introductionmentioning
confidence: 99%
“…(a) Simple models: the orientable stick model (19) and the sphero-cylindrical model (20). (b) Phenomenological models: the lattice model (21), Caflisch model (22), and Shea model (23). (c) Systematic coarse graining: a coarse-grained polyalanine chain (24).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the peptides that failed to aggregate demonstrated evidence of a lesser extent of antiparallel β-sheet structure tendency than the peptides that aggregated. Therefore, the localized primary perturbation of peptide structure exerted by the glutamine→proline mutations appears to result in a global secondary perturbation of peptide structural confinement, discouraging random conformational fluctuations which may be involved in the unfavourable transition towards β-sheet structure (Chopra et al, 2008;Bhattacharyya et al, 2005;Li et al, 2008), and so confining the peptide to an existing preference for the coil state. Indeed, introduction of such mutations into the polyQ segments of PGQ 9 would result in mutant polyQ sequences containing glutamine/proline-rich regions, in which intervals of only four or five residues separate consecutive prolines (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, our results provide a structural explanation for the inhibition of aggregation observed for these peptides. Indeed, a recent computational study by Vitalis et al (2008) proposed that a key factor in polyQ chain association is spontaneous conformational fluctuations within the polyQ monomer, and additional computational studies (Chopra et al, 2008;Li et al, 2008) have also suggested that spontaneous conformational fluctuation is involved in the transition toward β-sheet-like structure.…”
Section: Introductionmentioning
confidence: 97%
“…25 Each bead has mass m (m is the mass unit) and is connected to the neighboring beads in the peptide chain by harmonic ''springs.'' 25,[29][30][31][32] The force field used in our study has the following functional form:…”
Section: Coarse-grained Modelmentioning
confidence: 99%